Thanking and politeness in Japanese balancing acts in interaction - Ohashi, Jun; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This book synthesizes previous work on thanking, politeness and Japanese pragmatics and crystallises the theoretical underpinnings of thanking, how it is realized linguistically and the social meaning and significance of this aspect of Japanese communication.
Keywords: Literature; Oriental literature; Linguistics; Languages; Language and languages; Japanese language; Sociolinguistics; Pragmatics; Literature; Asian Literature; Asian Languages; Linguistics, general; Sociolinguistics; Japanese; Pragmatics